2020
DOI: 10.1002/dys.1666
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism, self‐stigma, and coping in students with dyslexia: The central role of perfectionistic self‐presentation

Abstract: Dyslexia is a prevalent condition, and a significant percentage of students in higher education are dyslexic. Despite this, few studies have investigated dyslexia in university students and what personality dispositions may predict how students feel about help‐seeking for dyslexia and how they cope with dyslexia. Against this background, the present study investigated perfectionism, self‐stigma, and coping in 115 university students with dyslexia, examining the relationships between dispositional perfectionism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…High achievement frustration suggests an emphasis on high standards, and an intolerance of the frustration of these standards (e.g., "I can't bear the frustration of not achieving my goals"). One previous study suggested that perfectionism self-presentation plays a central role in dyslexia (Stoeber & Rountree, 2020), and predicts negative reactions to impairment and disability (Read, Hill, Jowett, & Astill, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High achievement frustration suggests an emphasis on high standards, and an intolerance of the frustration of these standards (e.g., "I can't bear the frustration of not achieving my goals"). One previous study suggested that perfectionism self-presentation plays a central role in dyslexia (Stoeber & Rountree, 2020), and predicts negative reactions to impairment and disability (Read, Hill, Jowett, & Astill, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The latter are often described as extremely frustrated, owing to their inability (e.g., poor motor skills, academic failure) to meet their own and others' expectations (Abdul Hamid, Admodisastro, & Kamaruddin, 2015;Klassen et al, 2013). People with dyslexia may exhibit a low tolerance of difficulty (Sako, 2016), and a high level of perfectionism (Stoeber & Rountree, 2020). Thus, many of the emotional problems (e.g., feelings of low self-worth and incompetence; Gibby-Leversuch, Hartwell, & Wright, 2019) related to dyslexia occur out of frustration with school or social situations (Alexander-Passe, 2006;Al-Lamki, 2012;Jacobs, Parke, Ziegler, Headleand, & De Angeli, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The most common outcomes examined were self-esteem/self-worth (n = 7 studies), anxiety (n = 3 studies), depression (n = 2 studies), and a metric of academic performance (n = 4 studies). Of these 12 studies, seven occurred in the context of the USA (Daley & Rappolt-Schlichtmann, 2018;Fleming & Wated, 2016;Haft et al, 2019;Heyman, 1990;Hoehn, 1999; STIGMA IN SPECIFIC LEARNING DISABILITIES Maki, 2021;Thornton, 2020), three in the UK (Abraham et al, 2002;Stoeber & Rountree, 2021;Szivos, 1991), and two in China (Chan et al, 2017;Zhao et al, 2019).…”
Section: Stigma Studiesmentioning
confidence: 99%
“…Eight studies sampled participants in the childhood or adolescent age range (total of 508 participants; Chan et al, 2017;Daley & Rappolt-Schlichtmann, 2018;Haft et al, 2019;Heyman, 1990;Maki, 2021;Szivos, 1991;Thornton, 2020;Zhao et al, 2019), with the remaining four reporting data from adults (total of 428 participants; Abraham et al, 2002;Hoehn, 1999;Stoeber & Rountree, 2021;Szivos, 1991). Sex among the sample of individuals with SLDs was relatively balanced (45-55% female; 428 total participants) in only one of the studies (Maki, 2021)females were slightly overrepresented in the SLD sample in three of the studies (Abraham et al, 2002;Hoehn, 1999;Stoeber & Rountree, 2021), and were underrepresented in the SLD sample in seven of the studies (Chan et al, 2017;Daley & Rappolt-Schlichtmann, 2018;Haft et al, 2019;Heyman, 1990;Szivos, 1991;Thornton, 2020;Zhao et al, 2019). Half of the studies (n = 6) did not report the racial-ethnic composition of their sample of SLD participants.…”
Section: Stigma Studiesmentioning
confidence: 99%
See 1 more Smart Citation